2005
DOI: 10.1007/s00213-005-0132-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic–pituitary–adrenal axis and ethanol modulation of deoxycorticosterone levels in cynomolgus monkeys

Abstract: These results suggest that DOC levels in monkeys are regulated by the HPA axis and may contribute to physiological responses following activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 52 publications
3
41
0
Order By: Relevance
“…As described by Porcu et al (2006), training was conducted using positive reinforcement (fresh fruit) as the animal sat at the front of the cage and presented its leg through an opening (10 × 10 cm). Once comfortable, a dental pick was used to simulate a needle stick at the femoral vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Porcu et al (2006), training was conducted using positive reinforcement (fresh fruit) as the animal sat at the front of the cage and presented its leg through an opening (10 × 10 cm). Once comfortable, a dental pick was used to simulate a needle stick at the femoral vein.…”
Section: Methodsmentioning
confidence: 99%
“…After acute ethanol administration, the precursor to all steroid hormones, pregnenolone, was decreased in macaque monkeys (Porcu et al 2006) and increased in humans who were social drinkers (Pierucci-Lagha et al 2006). Likewise, following acute ethanol in cynomolgus monkeys or humans, the neuroactive steroid precursors progesterone and DOC, as well as the neuroactive metabolite 3α,5α-pregnanolone and the mineralocorticoid aldosterone are either not increased or are decreased (Porcu et al, 2006; 2010; Pierucci-Lagha et al 2006; Nieminen et al 1981). Lastly, ethanol challenge did not increase the neurosteroid DHEA in human males (Pierucci-Lagha et al 2006).…”
mentioning
confidence: 99%
“…DOC is an endogenous neuroactive steroid, synthesized from progesterone mainly in the adrenal glands but also in the brain; it is the precursor of the GABAergic neuroactive steroid 3α,5α-THDOC and of the glucocorticoid corticosterone. DOC levels are elevated in rat brain and mouse plasma following acute ethanol administration (Khisti et al 2005; Porcu et al 2010), are regulated by hypothalamic and pituitary activation of the HPA axis in both cynomolgus monkeys and humans and this regulation is altered following ethanol dependence (Porcu et al 2006; Porcu et al 2008). Across the BXD mouse population we found significant genetic variation in basal DOC levels.…”
Section: Genetic Variation In Neuroactive Steroid Levels Across Bxd Rmentioning
confidence: 99%
“…In humans, deoxycorticosterone plasma levels are increased following ACTH administration and decreased after dexamethasone administration (Brown and Strott, 1971;Tan and Mulrow, 1975;Kater et al, 1990), suggesting potential regulation by the hypothalamic-pituitary-adrenal (HPA) axis. In agreement, (Porcu et al 2006a) have shown that plasma deoxycorticosterone levels in cynomolgus monkeys are increased by naloxone and CRH challenges and decreased by dexamethasone challenge.…”
Section: Introductionmentioning
confidence: 54%
“…Deoxycorticosterone assay-Deoxycorticosterone levels were determined by RIAas previously described (Porcu et al, 2006a). Briefly, plasma samples (200 µl) were extracted twice with 2 ml ethyl acetate/hexane (3:2) 1000 cpm aliquot of [ 3 H]deoxycorticosterone (SpA = 50 Ci/mmol; American Radiolabeled Chemicals, Inc. Saint Louis, MO, USA) was added to each sample for recovery estimation.…”
Section: Dexamethasone Plus Cosyntropin Challengementioning
confidence: 99%